Teacher Evaluation within the Public Agenda - Minerva Nava Amaya; Mario Rueda Beltrán (Universidad Autónoma de Baja California, 2014)
The presence of the teacher performance evaluation in the public agenda is analyzed, indicating the role that the mass media have had in it. Is proposed to incorporate into the discussion elements from research experiences, in order to tackle the topic in a documented and analytical way. Considering the disparities of the educational scene, is indicated the need to provide the teacher of the indispensable conditions for his suitable performance, like a request before to the evaluation. The design and interpretation of evaluation results must consider the diversity of profiles, of institutional, sociocultural and economic contexts in which the teaching is exercised. Finally, some aspects are highlighted to consider in the design of politics and actions in order to favor the progress of the performance and the teaching evaluation.